Core outlet fuel temperature control of liquid molten salt reactor during load following operation. (March 2020) - Zeng, Wenjie; Jiang, Qingfeng; Xie, Jinsen; Yu, Tao
Abstract: As the molten salt fuel flows in the primary loop system of Liquid Molten Salt Reactor (LMSR), the core outlet fuel temperature can effectively characterize the core operation state. In this paper, a control strategy of the core outlet fuel temperature is designed based on the load power required. First, a nonlinear model of LMSR core is built by the lumped parameter method. Then, according to the relationship between the core outlet fuel temperature and the load power required, the control strategy of LMSR core outlet fuel temperature is established. The PID controller and the fuzzy PID controller are respectively used to design the core outlet fuel temperature control system. The simulation system is directly established by using the core nonlinear model. The simulation of LMSR core load following is carried out. The results show that the core outlet fuel temperature can be controlled well by using either PID controller or fuzzy PID controller. Highlights: A control strategy for the core outlet fuel temperature of Liquid Molten Salt Reactor is designed based on the load power required. The PID controller and the fuzzy PID controller are respectively used to design the core outlet fuel temperature control system of Liquid Molten Salt Reactor. The simulation system of core outlet fuel temperature control is directly established by using the core nonlinear model during load following operation.